A polyamide nanomembrane with precisely adjustable ordered pore structure and preparation method thereof

By using water-soluble polyamide dendrimers as additives in the preparation of polyamide nanofilms, a polyamide nanofilm with an ordered pore structure is solved, and the problems of uneven pore size distribution and weak electrostatic attraction effects in the prior art are solved, and efficient screening of ions with similar physical and chemical parameters is achieved.

CN119015897BActive Publication Date: 2025-02-28HENAN NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411506851.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-28
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing polyamide nanofilms have problems of uneven pore size distribution and weak electrostatic attraction effects in ion sieving, making it difficult to achieve fine screening of ions with similar physical and chemical parameters.

Method used

By using water-soluble polyamide dendrimers as additives, a stable colloid solution is formed and an oil-phase acyl chloride monomer is carried out for interfacial polymerization, and a polyamide nanofilm with an accurate and controllable ordered pore structure was prepared.

Benefits of technology

The order of the pore structure in the polyamide nanomembrane is increased and the pore size distribution is narrowed, which improves the efficient screening performance of ions, especially in the selectivity of Cl-/SO42- and Li+/Mg2+.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a polyamide nano-membrane with an ordered pore structure that is precisely adjustable and a preparation method thereof. Polyamide-amine dendritic macromolecules are used as additives to form a stable colloidal solution with aqueous amine monomers through hydrogen bonding, electrostatics or host-guest interactions, and a polyamide nano-membrane with an ordered pore structure that is precisely controllable is formed on the surface of a modified polysulfone-based membrane. The aqueous amine monomers are transformed from small molecule polyamines into colloids, which can improve the orderliness of the diffusion of the amine monomers, affect the stacking form of the polyamide polymer chain segments, increase the relative content of aggregated pores or mesh pores of the polyamide polymer chain segments, and regulate the orderliness of the sieve pore structure of the polyamide nano-membrane. The Cl of the polyamide nano-membrane regulated by low addition of dendritic macromolecules ‑ / SO4 2‑ Selectivity up to 4040, Li of polyamide nanomembrane regulated by high addition of dendrimers + / Mg 2+ Selectivity up to 278 with water permeate flux of 300‑500 L m ‑2 h ‑1 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of novel membrane separation materials, and in particular relates to a polyamide nano-membrane with an ordered pore structure that is precisely adjustable for ion screening and a preparation method thereof. Background Art

[0002] Ion screening is a common requirement of chemical industrial processes such as energy conversion and storage, clean industrial production, and resource recycling, involving important fields such as lithium extraction from salt lakes, brine refining (chlor-alkali industry), and high-salt wastewater resource utilization. For example, in order to achieve efficient lithium extraction from salt lake brine and realize Li + Cations coexisting with brine (Mg 2+ ) is very important; in the zero discharge process of industrial wastewater, Cl - and SO4 2- The precise separation seriously affects the energy consumption of the subsequent multiple-effect evaporator. Membrane separation technology represented by nanofiltration can achieve fine screening of nano / angstrom scale ions, while having the characteristics of high efficiency, energy saving, and environmental protection, and is expected to meet the urgent needs of my country's water, resources, and energy-related fields for the fine screening of diversified ions. Therefore, in response to major national needs such as energy conservation and emission reduction and the transformation and upgrading of traditional industries, the development of separation membrane materials for efficient ion screening is of great significance to the sustainable development of related chemical industrial processes.

[0003] At present, most commercial polyamide nanofiltration membranes are composed of a polymer porous support layer and a polyamide dense layer, in which the polyamide dense layer is prepared by interfacial polymerization of aqueous amine monomers and oil-phase acyl chloride monomers. During the interfacial polymerization process, the amine monomer diffuses into the organic phase and undergoes a Schotten-Baumann reaction with the acyl chloride monomer at the phase interface to form a polyamide polymer cross-linked network structure. Studies have confirmed that the ion screening performance of the polyamide nanomembrane is determined by the pore structure and internal charge of the polyamide dense layer, in which the pore structure is composed of stacked pores (aggregated pores) and mesh pores formed by polyamide polymer segments, while the internal charge is determined by the carboxyl groups and residual amino groups formed by the hydrolysis of acyl chloride groups that have not fully participated in the interfacial polymerization reaction. On the one hand, the polyamide nanomembrane structure formed by thermodynamic equilibrium control and rapid polymerization reaction has nanoscale heterogeneity and a wide pore size distribution, and it is difficult to finely screen ions with similar physicochemical parameters (such as Cl - / SO4 2- , Li + / Mg 2 + On the other hand, due to the diffusion-self-inhibition characteristics of the interfacial polymerization reaction, the polyamide nanomembrane has a high surface carboxyl density and strong negative charge, which has a strong electrostatic attraction to cations and is not conducive to the screening of monovalent / divalent cations.

[0004] Current research focuses on the regulation of the charge density of polyamide nanomembranes, designing monomers containing multi-charged groups, and introducing these molecules into the interior and surface of polyamide nanomembranes through interfacial polymerization or surface modification processes to enhance the charge repulsion effect and improve the ion selectivity of polyamide nanofiltration membranes. For example, patent CN 113694740A uses ionized quaternary ammonium salts as aqueous phase monomers to prepare polyamide membranes with high positive charge density inside the separation layer through interfacial polymerization; patents CN 117695873A, CN115105973A and CN 110026091A respectively introduce strong electrolyte monomers of quaternary ammonium salts and amino-functionalized ionic liquids into the surface of polyamide nanomembranes through secondary interfacial polymerization to prepare polyamide nanofiltration membranes with positive surface charge, and enhance their Li + / Mg 2+ Selectivity. However, the additional charged layer introduced by the surface modification method not only increases the thickness of the separation layer, resulting in the sacrifice of permeability; but also the strong charge shielding effect of the high-salt mixed solution leads to the destruction of its ion selectivity. Therefore, how to accurately control the microstructure of the polyamide nanomembrane and increase the order of the sieving pore size is the key to designing and preparing fine ion sieving membranes.

[0005] The main strategy for regulating the pore structure of polyamide nanomembranes is to regulate the interfacial polymerization process by means of additives or by constructing an intermediate layer. For example, patent CN 116585912A constructs a dendritic macromolecular intermediate layer with high positive charge density, regulates the diffusion and distribution of amine monomers, and prepares polyamide nanomembranes with narrow pore size distribution. When used for mixed salt testing, its Li + The retention rate is less than 15%, Mg 2+ The interception rate is above 98%, Li + / Mg 2+ The selectivity is 40-100. Patents CN 113262642A and CN112755817A use surfactants (such as sodium dodecyl sulfonate and phosphodiester compounds) to self-assemble monolayers at the water-oil interface to regulate the diffusion of amine monomers to prepare polyamide membranes with uniform pore structures. The prepared polyamide nanomembrane with narrow pore size distribution has a divalent cation retention rate higher than 98.5%, a monovalent cation retention rate lower than 35%, and a water flux that can be maintained at These studies show that the regulation of the pore structure of polyamide nanomembranes is extremely important for improving the ion screening performance. However, there are currently no reports on the controllable regulation of the orderliness of the pore structure of polyamide membranes. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a polyamide nanomembrane with an ordered pore structure that can be precisely controlled, so as to achieve a "tailor-made" preparation of a polyamide nanomembrane with high-efficiency ion screening performance. The present invention proposes a technical solution in which water-soluble polyamide dendritic macromolecules are used as additives to form a stable colloidal solution with aqueous amine monomers through hydrogen bonds, electrostatics or host-guest interactions, and then form a polyamide nanomembrane with an ordered pore structure that is precisely controllable on the surface of a modified polysulfone-based membrane through an interfacial polymerization reaction. The invention controls the stacked pores or mesh pores (such as Figure 1 The relative content of (as shown) can be precisely controlled to achieve the order of the pore structure in the polyamide nanomembrane.

[0007] The present invention provides a method for preparing a polyamide nano-membrane with an ordered pore structure that is precisely adjustable. The polyamide nano-membrane is formed on a modified polysulfone-based membrane by an interfacial polymerization reaction of a colloidal solution composed of water-soluble polyamide-amine dendritic macromolecules and an aqueous amine monomer and an oil-phase acyl chloride monomer solution. The polyamide nano-membrane has a precisely controllable ordered pore structure and can achieve efficient ion screening.

[0008] Furthermore, the water-soluble polyamide-amine dendrimer is a polyamide-amine dendrimer terminated by carboxyl, hydroxyl or phenolic hydroxyl groups, the colloidal solution is formed by the polyamide-amine dendrimer terminated by carboxyl, hydroxyl or phenolic hydroxyl groups and the polyamine monomer through hydrogen bonding, electrostatic or host-guest interaction, and the polyamide-amine dendrimer terminated by carboxyl, hydroxyl or phenolic hydroxyl groups is composed of an inner core G0, an aliphatic polyamide branching structure G1-G2, and a polyamide branching structure G2-G3. n-1 and the end-capping molecular structure is G n wherein n is the iteration number of the dendritic macromolecule, and n is 1-7. The general formula of the polyamide-amine dendritic macromolecule terminated by carboxyl, hydroxyl or phenolic hydroxyl is as follows:

[0009]

[0010] Among them, the structure of kernel G0 is:

[0011]

[0012] The branched structure of aliphatic polyamide is formed by the Michael addition reaction of ethylenediamine methyl acrylate to form a tetraester, which is then condensed with excess ethylenediamine to form G1-G n-1 The branched structure is:

[0013]

[0014] The end-capping molecule is one of ethylene glycol anhydride, succinic anhydride, 1,2,4-benzoic anhydride, ethanolamine or p-hydroxybenzoyl chloride, G n The structure is: One of them.

[0015] Furthermore, the polyamine monomer is one of piperazine, tri(2-aminoethyl)amine, triethylenetetramine, tetraethylenepentamine, pentaerythritoldiamine, polymer-bonded ethylenediamine, 1,2-diaminocyclohexane or cyclohexane-1,4-diamine.

[0016] Furthermore, the oil phase acyl chloride monomer is one of trimesoyl chloride, 1, 2, 3, 4-cyclobutanetetracarboxylic acid chloride or 1, 2,3, 4-cyclopentanetetracarboxylic acid chloride, the solution concentration of the oil phase acyl chloride monomer is 0.05-0.5 wt%, and the oil phase solvent is one of cyclohexane, n-hexane, n-heptane, n-octane or ISOPAR-G.

[0017] Further, the preparation method of the modified polysulfone-based membrane is as follows: the polysulfone-based membrane is immersed in a 0.01 w / v% 32-amine-terminated polyamide dendritic macromolecule acidic solution for 30 min, pH 1.0-2.0, and after removing the excess solution, it is immersed in a 0.5 w / v% sodium nitrite acidic solution for 5 min, pH 1.5-2.5, and the excess solution is removed, and then the modified base membrane is immersed in deionized water; wherein the structural formula of the 32-amine-terminated polyamide dendritic macromolecule is:

[0018]

[0019] Further, the ion screening performance of the polyamide nanomembrane was tested: when evaluating the nanofiltration performance, the feed liquid was a 2000 ppm single salt solution (such as Na2SO4, NaCl, MgCl2 and LiCl), and the test pressure was 145 psi; when evaluating Cl - / SO4 2- The feed solution was a mixed salt solution of 2000 ppm Na2SO4 and 2000 ppm NaCl, and the test pressure was 145 psi. + / Mg 2+ When the feed solution is a mixed solution of 134 ppm LiCl and 1866 ppm MgCl2, the Mg 2+ With Li + The mass ratio of is 21.4, and the test pressure is 145 psi. The test temperature is 25 °C. Under cross-flow conditions, the prepared polyamide membrane is pre-pressed for 2 h. Ion chromatography is used to test the ion concentrations in the permeate and the raw material solution, respectively. The ion screening selectivity is calculated according to the following formula:

[0020] ;

[0021] .

[0022] The present invention provides a method for preparing the above-mentioned polyamide nanomembrane with an ordered pore structure that is precisely adjustable, comprising the following steps: (1) adding carboxyl-, hydroxyl- or phenolic-hydroxyl-terminated polyamide-amine dendritic macromolecules into a polyamine aqueous phase to form a colloidal solution; (2) soaking a modified polysulfone-based membrane in the above-mentioned colloidal solution, and then soaking it in an oil-phase acyl chloride monomer solution, and then washing and subsequently drying to obtain the polyamide nanomembrane.

[0023] Further, specifically, the method comprises the following steps: (1) stirring a polyamide-amine dendrimer terminated by carboxyl, hydroxyl or phenolic hydroxyl groups and a polyamine monomer in water for 2-10 min to form a stable colloidal solution through hydrogen bonding, electrostatic or host-guest interaction, wherein the concentration of the dendrimer terminated by carboxyl, hydroxyl or phenolic hydroxyl groups is 0.01-0.15 wt %, and the concentration of the polyamine monomer solution is 0.5-2.0 wt %; (2) soaking the modified polysulfone-based membrane in the above colloidal solution for 2-5 min, removing the residual aqueous solution, and then soaking it in an oil-phase acyl chloride monomer solution for 30-120 s, removing the excess oil-phase solution, and then immediately washing with an oil-phase organic solvent for 10-40 s to remove the unreacted acyl chloride monomer, and then placing it in a 50-70 °C oven for further crosslinking for 2-10 min to obtain the polyamide nanomembrane.

[0024] Furthermore, the polyamide-amine dendritic macromolecules terminated by carboxyl, hydroxyl or phenolic hydroxyl groups form a colloid with the polyamine monomers and participate in the interfacial polymerization reaction together; at the interface, they not only occupy the reaction sites and regulate the diffusion of the polyamine monomers; but also are doped into the interior of the polyamide nanomembrane, affecting the stacking mode of the polyamide polymer chain segments, increasing the relative content of the aggregated pores or mesh pores of the polyamide polymer chain segments, regulating the order of the sieve pore structure of the polyamide nanomembrane, and the pore size distribution is narrow.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention starts from the form of the water-phase amine monomer participating in the interfacial polymerization reaction, and uses the water-soluble dendritic macromolecules with orderly and regular pore structures and peripheral functionalization to regulate the form of the water-phase amine monomer participating in the interfacial polymerization reaction, transforming from polyamine small molecules to colloidal macromolecules, which can not only improve the orderliness of the diffusion of amine monomers and coordinate the pore size distribution of the formed polyamide nanomembrane; but also can be doped into the polyamide nanomembrane, affecting the stacking form of the polyamide polymer chain segments, increasing the relative content of the aggregated pores or mesh pores of the polyamide polymer chain segments, and regulating the orderliness of the sieve pore structure of the polyamide nanomembrane. Therefore, the fundamental feature of the present invention is that the prepared polyamide nanomembrane has an increased ordered pore structure and a narrowed pore size distribution.

[0027] (2) By adjusting the amount of dendritic macromolecules added, the pore structure of the polyamide nanomembrane, i.e., the effective pore size and pore size distribution, can be continuously controlled, so as to achieve a "tailor-made" preparation of polyamide nanomembranes that meet the requirements of different ion screening. For example, when the amount of dendritic macromolecules added is low, the proportion of mesh pores in the polyamide polymer chain segments in the prepared polyamide nanomembrane increases, and the pore size distribution narrows. Under the above single salt test conditions, the Na2SO4 retention rate is 99%-99.51%, the NaCl retention rate is 12.1%-30%, and the water permeation flux is 300-500 Lm -2 h -1 Under the above-mentioned conditions for measuring monovalent / divalent anion selectivity, its Cl - The interception rate is -10%--50%, SO4 2- The retention rate is between 99.21% and 99.93%, and the Cl calculated from this - / SO4 2- The selectivity is 1068.55-4040.68, which is much better than the currently reported ion selective membranes, indicating that the membrane preparation method of the present invention has significant technical progress.

[0028] (3) When the amount of dendrimer added is high, more reaction sites are occupied at the interface, the proportion of stacked pores in the polyamide polymer chain segments increases significantly, and the pore size distribution narrows significantly. Under the above single salt test conditions, the LiCl retention rate is 20%-40%, the MgCl2 retention rate is higher than 97%, and the water permeation flux is 300-500 L m -2 h -1 Under the above conditions for measuring monovalent / divalent cation selectivity, its Li - The retention rate is -10%-27%, Mg 2+ The interception rate is between 98.98% and 99.74%, and the Li + / Mg 2+ The selectivity is 167.1-278.77, and it has excellent lithium and magnesium screening selection performance, which is far superior to the currently reported nanofiltration membranes, indicating that the membrane preparation method of the present invention has significant technical progress.

[0029] (4) The preparation method of the polyamide nanomembrane with precisely controllable ordered pore structure provided by the present invention is simple, and the preparation process is easy to scale up and promote in industry. It can be used in processes such as brine refining, lithium extraction from salt lakes / brine, water softening and heavy metal wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the network cross-linked structure of interfacially polymerized polyamide polymer chain segments. The sieving pore size of the polyamide nanomembrane is composed of aggregated pores and network pores formed by the polyamide polymer chain segments.

[0031] Figure 2 This is a Tyndall effect diagram of the aqueous colloidal solution prepared in Example 4 of the present invention.

[0032] Figure 3 The Zeta potential diagram of the 64-carboxyl-terminated dendrimer designed for the present invention in aqueous solution, with a concentration of 0.08 wt%, shows that the Zeta potential is negative due to the abundant carboxyl groups on the periphery.

[0033] Figure 4 This is the Zeta potential diagram of the aqueous colloidal solution prepared in Example 12 of the present invention. The 64-carboxyl-terminated dendritic macromolecules have abundant carboxyl groups on the periphery, which are easily protonated and form colloids with the polyamine monomers in the aqueous solution through hydrogen bonds or electrostatic interactions. The periphery of the colloid is rich in polyamine monomers, so the Zeta potential of the colloidal solution is positive.

[0034] Figure 5 This is a surface SEM morphology of the polyamide nanomembrane prepared in Example 6 of the present invention. The surface presents nano-stripes and nanoparticles with an ordered pore structure. These nanoparticles originate from colloidal particles assembled from dendritic macromolecules and are in-situ incorporated into the polyamide nanomembrane through interfacial polymerization.

[0035] Figure 6 The pore size distribution of the polyamide nanomembranes prepared in Comparative Example 1 and Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0036] The technical solution created by the present invention is further explained and illustrated below in conjunction with specific embodiments.

[0037] To ensure that the base membrane has the same effect on the permeability and selectivity of the composite membrane, the preparation methods of the modified polysulfone-based membranes in the following comparative examples and embodiments are exactly the same. Based on the in-situ covalent grafting of 3,2-amino-terminated polyamide dendritic macromolecules with diazonium salt chemistry, the surface pore structure and chemical properties of the polysulfone-based membrane are optimized by constructing a dendritic macromolecule intermediate layer. The specific process of the preparation method of the modified polysulfone-based membrane is as follows: the polysulfone-based membrane is immersed in a 0.01 w / v% 3,2-amino-terminated polyamide dendritic macromolecule acidic solution (pH 1.0-2.0) for 30 min, and after removing the excess solution, it is immersed in a 0.5 w / v% sodium nitrite acidic solution (pH1.5-2.5) for 5 min, and the excess solution is removed, and it is immersed in deionized water. The structural formula of the 6,4-amino-terminated polyamide dendritic macromolecule is:

[0038]

[0039] Comparative Example 1:

[0040] The comparative example shows a method for preparing a conventional polyamide nanomembrane. Compared with the embodiment, the main difference is that no dendritic macromolecules are added to the aqueous phase solution, and the other preparation parameters and processes are exactly the same. The specific preparation process is: immerse the above-mentioned modified polysulfone-based membrane in a 0.8 wt% piperazine aqueous phase solution for 2 min, remove the excess solution with a rubber roller, and then further immerse it in a 0.1 w / v% hexane solution of trimesoyl chloride for 30 s to form a dense layer of polyamide, then wash it with hexane solvent for 30 s, and place it in a 60 ° C oven for heat treatment for 2 min to obtain a conventional polyamide nanomembrane. Finally, the obtained polyamide nanomembrane was tested for single salt and mixed salt to evaluate its nanofiltration performance, Cl - / SO4 2- Selectivity and Li + / Mg 2+ Selective.

[0041] Embodiment 1:

[0042] Preparation of aqueous colloidal solution: The 64-carboxyl-terminated dendrimer and piperazine monomer of the following structure were stirred in aqueous solution for 5 min to prepare an aqueous colloidal solution, wherein the concentration of the 64-carboxyl-terminated dendrimer was 0.02 wt% and the concentration of piperazine was 0.8 wt%.

[0043] The specific structure of the 64-carboxyl-terminated dendrimer is as follows:

[0044]

[0045] Preparation of polyamide nanomembrane with precisely adjustable ordered pore structure: The modified polysulfone-based membrane was immersed in the aqueous colloidal solution prepared above for 2 min, and the excess solution was removed with a rubber roller; then, it was immersed in a 0.1 w / v% hexane solution of trimesoyl chloride for 30 s to form a dense polyamide layer, and then immersed in a hexane solvent for washing for 30 s and placed in a 60 °C oven for heat treatment for 2 min. Finally, the obtained polyamide nanomembrane was subjected to nanofiltration and ion sieving performance evaluation experiments.

[0046] Embodiment 2:

[0047] The concentration of 64-carboxyl-terminated dendrimers was replaced with 0.04, and the other conditions were the same as in Example 1.

[0048] Embodiment 3:

[0049] The concentration of 64-carboxyl-terminated dendrimers was replaced with 0.1, and the other conditions were the same as in Example 1.

[0050] Embodiment 4:

[0051] Preparation of aqueous colloidal solution: The 128-carboxyl-terminated dendrimer and piperazine monomer of the following structure were stirred in aqueous solution for 10 min to prepare an aqueous colloidal solution, wherein the concentration of the 128-carboxyl-terminated dendrimer was 0.02 wt % and the concentration of piperazine was 0.8 wt %.

[0052] The specific structure of the 128-carboxyl-terminated dendrimer is as follows:

[0053]

[0054] Preparation of polyamide nanomembrane with precisely adjustable ordered pore structure: The modified polysulfone-based membrane was immersed in the aqueous colloidal solution prepared above for 2 min, and the excess solution was removed with a rubber roller; then, it was immersed in a 0.1 w / v% hexane solution of trimesoyl chloride for 30 s to form a dense polyamide layer, and then immersed in a hexane solvent for washing for 30 s and placed in a 60 °C oven for heat treatment for 2 min. Finally, the obtained polyamide nanomembrane was subjected to nanofiltration and ion sieving performance evaluation experiments.

[0055] Embodiment 5:

[0056] The concentration of 128-carboxyl-terminated dendrimers was replaced with 0.08, and the other conditions were the same as those in Example 4.

[0057] Embodiment 6:

[0058] Preparation of aqueous colloidal solution: The 128-hydroxyl-terminated dendrimer and piperazine monomer of the following structure were stirred in aqueous solution for 10 min to prepare an aqueous colloidal solution, wherein the concentration of the 128-hydroxyl-terminated dendrimer was 0.03 wt % and the concentration of piperazine was 0.8 wt %.

[0059] The specific structure of the 128-hydroxyl-terminated dendrimer is as follows:

[0060]

[0061] Preparation of polyamide nanomembrane with precisely adjustable ordered pore structure: The modified polysulfone-based membrane was immersed in the aqueous colloidal solution prepared above for 2 min, and the excess solution was removed with a rubber roller; then, it was immersed in a 0.1 w / v% hexane solution of trimesoyl chloride for 30 s to form a dense polyamide layer, and then immersed in a hexane solvent for washing for 30 s and placed in a 60 °C oven for heat treatment for 2 min. Finally, the obtained polyamide nanomembrane was subjected to nanofiltration and ion sieving performance evaluation experiments.

[0062] Embodiment 7:

[0063] The concentration of 128-hydroxyl-terminated dendrimer was replaced with 0.08, and the other conditions were the same as those in Example 6.

[0064] Embodiment 8:

[0065] Preparation of aqueous colloidal solution: The 128-phenolic hydroxyl-terminated dendrimer and piperazine monomer of the following structure were stirred in aqueous solution for 10 min to prepare an aqueous colloidal solution, wherein the concentration of the 128-phenolic hydroxyl-terminated dendrimer was 0.03 wt% and the concentration of piperazine was 0.8 wt%.

[0066] The specific structure of the 128-phenolic hydroxyl-terminated dendrimer is as follows:

[0067]

[0068] Preparation of polyamide nanomembrane with precisely adjustable ordered pore structure: The modified polysulfone-based membrane was immersed in the aqueous colloidal solution prepared above for 2 min, and the excess solution was removed with a rubber roller; then, it was immersed in a 0.1 w / v% hexane solution of trimesoyl chloride for 30 s to form a dense polyamide layer, and then immersed in a hexane solvent for washing for 30 s and placed in a 60 °C oven for heat treatment for 2 min. Finally, the obtained polyamide nanomembrane was subjected to nanofiltration and ion sieving performance evaluation experiments.

[0069] Embodiment 9:

[0070] The concentration of 128-phenolic hydroxyl-terminated dendrimers was replaced with 0.08, and the other conditions were the same as those in Example 8.

[0071] Embodiment 10:

[0072] Preparation of aqueous colloidal solution: The 6,4-carboxyl-terminated dendrimer and tri(2-aminoethyl)amine monomer of the following structure were stirred in an aqueous solution for 10 min to prepare an aqueous colloidal solution, wherein the concentration of the 6,4-carboxyl-terminated dendrimer was 0.02 wt% and the concentration of the tri(2-aminoethyl)amine was 1.0 wt%.

[0073] Preparation of polyamide nanomembrane with precisely adjustable ordered pore structure: The modified polysulfone-based membrane was immersed in the aqueous colloidal solution prepared above for 2 min, and the excess solution was removed with a rubber roller; then, it was immersed in a 0.1 w / v% hexane solution of trimesoyl chloride for 30 s to form a dense polyamide layer, and then immersed in a hexane solvent for washing for 30 s and placed in a 60 °C oven for heat treatment for 2 min. Finally, the obtained polyamide nanomembrane was subjected to nanofiltration and ion sieving performance evaluation experiments.

[0074] Embodiment 11:

[0075] The concentration of 64-carboxyl-terminated dendrimer was replaced with 0.1, and the other conditions were the same as in Example 10.

[0076] The separation performance of the polyamide membrane prepared in the present invention is shown in Tables 1 and 2.

[0077] Table 1 Nanofiltration separation and monovalent / divalent anion selectivity of the polyamide nanomembrane prepared in the present invention

[0078]

[0079] a Test conditions: 2000 ppm Na2SO4 or NaCl aqueous solution as the test solution, at 145 psi operating pressure, 25°C, and after pre-pressing for 2 h, the nanofiltration separation performance was tested.

[0080] b Test conditions: 2000 ppm Na2SO4 and 2000 ppm NaCl mixed brine solution as test solution, 145 psi operating pressure, 25°C, pre-press for 1 h before testing Cl - and SO4 2- Retention rate and calculate Cl - / SO4 2- Selective.

[0081] As can be seen from Table 1, the polyamide nanoparticles with increased ordered pore structure prepared by the present invention have a low SO42- The retention rates of Cl - The interception rate is less than 16.02%, Cl - / SO4 2- The selectivity is more than ten times higher than that of the control group. In particular, when the amount of dendritic macromolecules added is low, the prepared polyamide nanomembranes (such as Examples 2, 4, 6 and 8) have a Cl - / SO4 2- The selectivity was as high as 3580.25-4040.88, and the permeate flux was 341.89-431.49 L m -2 h -1 , which is much higher than the polyamide nanofiltration membrane reported in the literature, and can be applied to the zero-emission treatment process of industrial wastewater generated by chlor-alkali or coal chemical industry, hydrometallurgy, pharmaceutical and other industries.

[0082] Table 2 Lithium and magnesium screening performance of the polyamide nanomembrane prepared in the present invention.

[0083]

[0084] c Test conditions: 2000 ppm MgCl2 or LiCl aqueous solution was used as the test solution. The prepared polyamide membrane was pre-pressed for 2 h at 145 psi operating pressure and 25 °C to test the nanofiltration separation performance.

[0085] d Test conditions: 134 ppm MgCl2 and 1866 ppm LiCl mixed brine solution was used as the test solution, the mass ratio of magnesium to lithium in the original solution was 21.4, the prepared polyamide membrane was pre-pressed for 1 h at 145 psi operating pressure and 25°C, and the Li + and Mg 2+ Retention rate, and calculate Li + / Mg 2+ Selective.

[0086] As can be seen from Table 2, under the mixed salt solution test conditions, the polyamide nanofilm prepared with high addition of dendritic macromolecules has high Mg 2+ Rejection rate (greater than 99.45%) and lower Li + Retention rate (less than 27.39%), calculated Li + / Mg 2+ The selectivity is 167.1-278.77, indicating that the nano-membrane obtained by the present invention has application potential in lithium-magnesium separation and can be applied to efficient screening of lithium extraction from salt lakes.

Claims

1. A polyamide nanomembrane with an ordered pore structure that is precisely adjustable, characterized in that: The polyamide nanomembrane is formed on a modified polysulfone-based membrane by an interfacial polymerization reaction of a colloidal solution composed of a water-soluble polyamide-amine dendritic macromolecule and an aqueous amine monomer and an oil-phase acyl chloride monomer solution. The polyamide nanomembrane has a precisely controllable ordered pore structure and a narrow pore size distribution, and can achieve efficient ion screening. The water-soluble polyamide-amine dendritic macromolecule is a polyamide-amine dendritic macromolecule terminated by carboxyl, hydroxyl or phenolic hydroxyl groups, the colloidal solution is formed by a polyamide-amine dendritic macromolecule terminated by carboxyl, hydroxyl or phenolic hydroxyl groups and a polyamine monomer through hydrogen bonding, electrostatics or host-guest interaction, and the polyamide-amine dendritic macromolecule terminated by carboxyl, hydroxyl or phenolic hydroxyl groups is composed of an inner core G0, an aliphatic polyamide branching structure G1-G2, and a branched structure G1-G3. n-1 and the end-capping molecular structure is G n wherein n is the iteration number of the dendritic macromolecule, and n is 1-7. The general formula of the polyamide-amine dendritic macromolecule terminated by carboxyl, hydroxyl or phenolic hydroxyl is as follows: Among them, the structure of kernel G0 is: Among them, the branched structure of aliphatic polyamide is formed by the Michael addition reaction of ethylenediamine methyl acrylate to form a tetraester, which is then condensed with excess ethylenediamine to form G1-G n-1 The branched structure is: The end-capping molecule is one of ethylene glycol anhydride, succinic anhydride, 1,2,4-benzoic anhydride, ethanolamine or p-hydroxybenzoyl chloride, G n The structure is: One of them.

2. A polyamide nanomembrane with an ordered pore structure that is precisely adjustable according to claim 1, characterized in that: The polyamine monomer is one of piperazine, tris(2-aminoethyl)amine, triethylenetetramine, tetraethylenepentamine, pentaerythritoldiamine, polymer-bonded ethylenediamine, 1,2-diaminocyclohexane or cyclohexane-1,4-diamine.

3. A polyamide nanomembrane with an ordered pore structure that is precisely adjustable according to claim 2, characterized in that: The oil phase acyl chloride monomer is one of trimesoyl chloride, 1,2,3,4-cyclobutanetetracarboxylic acid chloride or 1,2,3,4-cyclopentanetetracarboxylic acid chloride, the solution concentration of the oil phase acyl chloride monomer is 0.05-0.5wt%, and the oil phase solvent is one of cyclohexane, n-hexane, n-heptane, n-octane or ISOPAR-G.

4. A polyamide nanomembrane with an ordered pore structure that is precisely adjustable according to claim 3, characterized in that: The preparation method of the modified polysulfone-based membrane is as follows: the polysulfone-based membrane is immersed in a 0.01w / v% 32-amine-terminated polyamide dendritic macromolecule acidic solution for 30 minutes, pH 1.0-2.0, and after removing the excess solution, it is immersed in a 0.5w / v% sodium nitrite solution for 5 minutes, pH 1.5-2.5, and then the excess solution is removed. Then, the modified base membrane is immersed in deionized water; wherein the structural formula of the 32-amine-terminated polyamide dendritic macromolecule is:

5. A polyamide nanomembrane with an ordered pore structure that is precisely adjustable according to claim 4, characterized in that: The Cl - / SO4 2- The selectivity is 1068.55-4040.68, Li + / Mg 2+ The selectivity is 167.1-278.77, and the water permeate flux is 300-500 L m -2 h -1 .

6. The method for preparing a polyamide nanofilm with an ordered pore structure that is precisely adjustable according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Stirring polyamide-amine dendrimers terminated by carboxyl, hydroxyl or phenolic hydroxyl groups and polyamine monomers in water for 2-10 minutes to form a stable colloidal solution through hydrogen bonding, electrostatic or host-guest interaction, wherein the concentration of the dendrimers terminated by carboxyl, hydroxyl or phenolic hydroxyl groups is 0.01-0.15wt%, and the concentration of the polyamine monomer solution is 0.5-2.0wt%; (2) Soaking the modified polysulfone-based membrane in the above colloidal solution for 2-5 minutes, removing the residual aqueous solution, and then soaking it in an oil-phase acyl chloride monomer solution for 30-120 seconds to remove the excess oil-phase solution, and then immediately washing it with an oil-phase organic solvent for 10-40 seconds to remove the unreacted acyl chloride monomer, and then placing it in an oven at 50-70° C. for further crosslinking for 2-10 minutes to obtain the polyamide nanomembrane; wherein the polyamide-amine dendrimers terminated by carboxyl, hydroxyl or phenolic hydroxyl groups and the polyamine monomers form a colloid and participate in the interfacial polymerization reaction together; At the interface, it not only occupies the reaction site and regulates the diffusion of the polyamine monomer; but also is doped inside the polyamide nanomembrane, affecting the stacking mode of the polyamide polymer chain segments, increasing the relative content of the aggregated pores or mesh pores of the polyamide polymer chain segments, regulating the order of the sieve pore structure of the polyamide nanomembrane, and having a narrow pore size distribution.

Citation Information

Patent Citations

  • Ionic liquid modified positively charged composite nanofiltration membrane and preparation method thereof

    CN110026091A

  • Composite nanofiltration membrane with high performance as well as preparation method and application of composite nanofiltration membrane

    CN112755817A

  • Nanofiltration membrane with ultrahigh separation selectivity and preparation method and application thereof

    CN113262642A

  • Positively charged nanofiltration membrane prepared from ionized monomer and preparation method thereof

    CN113694740A

  • Preparation method and application of nanofiltration membrane for efficient magnesium-lithium separation

    CN115105973A